2020
DOI: 10.1002/lary.28971
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Hearing Loss Progression and Asymmetry in the Older Old: A National Population‐Based Study

Abstract: The progression and asymmetry of age-related hearing loss has not been well characterized in those 80 years of age and older because public datasets mask upper extremes of age to protect anonymity. We aim to characterize the progression, severity, and asymmetry of hearing loss in those 80 years of age and older using a representative, national database. Methods: Cross-sectional, multicentered U.S. epidemiologic analysis using the National Health and Nutrition Examination Survey (NHANES) 2005 to 2006, 2009 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
(43 reference statements)
2
8
0
Order By: Relevance
“…Although ARHL is typically bilateral and symmetric, the symmetry is imperfect, conveniently providing variation to study whether the right or left ear may have asymmetrical effects (6,16). The concepts of “right ear advantage” and hemispheric lateralization may support the findings of this study.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Although ARHL is typically bilateral and symmetric, the symmetry is imperfect, conveniently providing variation to study whether the right or left ear may have asymmetrical effects (6,16). The concepts of “right ear advantage” and hemispheric lateralization may support the findings of this study.…”
Section: Discussionsupporting
confidence: 57%
“…It involves both ears and first affects perception of high frequency sounds, successively followed by lower frequencies. ARHL is highly prevalent, affecting nearly 50% of adults ages 60 to 69 and over 80% of those over 85 years old (1)(2)(3)(4)(5)(6). Moreover, ARHL has been linked to conditions of aging including dementia (7)(8)(9) and depression (9)(10)(11)(12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pure tone asymmetry may increase with age. 28 The three groups included in the present study showed a significant difference in the mean age. In average, the difference between ages in the non-noise-exposed group and 15-year noise-exposed group was 17.7 years.…”
Section: Discussionmentioning
confidence: 58%
“…Given that age-related hearing loss is associated with increased risk of incident dementia [1] , [2] , [3] and depressive symptoms [ 4 , 5 ], prompt diagnosis and intervention is important. In addition, the older population is rapidly growing [6] and better characterization of hearing loss in adults ≥80 years old is needed, as public datasets sometimes mask the upper extremes of age to protect anonymity [7] . In this issue, Koichiro Wasano and colleagues descriptively analyze how hearing thresholds, or the softest sound levels an individual can hear, change throughout the lifespan in a large sample of Japanese patients visiting an otolaryngology department [8] .…”
mentioning
confidence: 99%